ANALISIS KEPATUHAN PAJAK: DAMPAK ETIKA, KONTROL PERILAKU DAN PENGETAHUAN WAJIB PAJAK - Deden Tarmidi; Devi Lucianah Nurlita (Universitas 17 Agustus 1945 Jakarta, 2018)
The purpose of this study is to determine the influence of ethics, behavior control and knowledge of tax professional on tax compliance, that’s because tax compliance in Indonesia is still low. The variables and the measurement used in this study are addopted from some previous research such as Astuti & Panjaitan (2017), Husnurrosyidah & Suhadi (2017), Putra (2017), Rahayu (2017), Sudrajat & Ompusunggu (2015), Zuhdi et al., (2015), Tarmidi & Waluyo (2014), Alvin (2014), Damayanti & Martono (2018), Cahyonowati et al., (2012) with minor modifications. One hundred tax professionals as taxpayer representatives in KPP Pratama Jakarta Cengkareng has been the sample of this research by convenience sampling method. Structural Equation Modeling (SEM) by SmartPLS3 used for analyzed variables data of this study. The results showed that ethics, behavior control and knowledge have positive influence on tax compliance.These empirical results explain that tax payer or tax professional can be tax payer compliance when have a good ethics, behavior control and good tax knowledge, these also can be information to Government for increasing tax compliance in Indonesia.Key Words : tax compliance, ethics, behavior control, knowledge